Transforming Human Resources: The Key to Revolutionizing Indonesian Legal Reform and Justice System Efficiency - Hilal, Maulidi; Purnomo, Arif; Arief, Sandy (Journal of Law and Legal Reform, 2024)
Indonesia’s legal reform and justice system have long faced challenges of inefficiency, corruption, and a lack of skilled personnel. As the nation strives to modernize and improve governance, a transformative approach is necessary to address systemic shortcomings. This research explores the pivotal role of Human Resources (HR) management in reshaping the Indonesian justice system, arguing that reforms in HR practices are essential to achieving sustainable legal reform and enhancing judicial efficiency. The study introduces a novel perspective by linking HR practices—such as recruitment, training, performance management, and retention—with broader goals of institutional transformation and legal accountability. The urgency of this research lies in Indonesia’s ongoing efforts to combat corruption and improve the public sector’s effectiveness. HR reforms are positioned as a key lever for institutional change, offering a pathway to ensure that the judicial system is staffed with competent, ethical, and efficient personnel. The research examines existing HR practices within the justice sector and proposes innovative strategies for talent development, capacity building, and alignment with international standards. By fostering a culture of accountability and professionalism, these reforms can contribute to increased public trust and a more equitable legal environment. This study makes a significant contribution by bridging the gap between HR management and judicial reform in Indonesia. It provides actionable insights for policymakers, legal professionals, and international partners, emphasizing that an investment in human capital is central to achieving a more effective, transparent, and just legal system. Ultimately, the research underscores that HR transformation is not just an administrative reform, but a critical element in the broader pursuit of justice and national development.